mig-38, a novel gene that regulates distal tip cell turning during gonadogenesis in C. elegans hermaphrodites - Martynovsky, Maria (2012)
In Caenorhabditis elegans gonad morphogenesis, the final U-shapes of the two hermaphrodite gonad arms are determined by migration of the distal tip cells (DTCs). These somatic cells migrate in opposite directions on the ventral basement membrane until specific extracellular cues induce turning from ventral to dorsal and then centripetally toward the midbody region on the dorsal basement membrane. To dissect the mechanism of DTC turning, we examined the role of a novel gene, F40F11.2/mig-38, whose depletion by RNAi results in failure of DTC turning so that DTCs continue their migration away from the midbody region. mig-38 is expressed in the gonad primordium, and expression continues throughout DTC migration where it acts cell-autonomously to control DTC turning. RNAi depletion of both mig-38 and ina-1, which encodes an integrin adhesion receptor, enhanced the loss of turning phenotype indicating a genetic interaction between these genes. Furthermore, the integrin-associated protein MIG-15/Nck-interacting kinase (NIK) works with MIG-38 to direct DTC turning as shown by mig-38 RNAi with the mig-15(rh80) hypomorph. These results indicate that MIG-38 enhances the role of MIG-15 in integrin-dependent DTC turning. Knockdown of talin, a protein that is important for integrin activation, causes the DTCs to stop migration prematurely. When both talin and MIG-38 were depleted by RNAi treatment, the premature stop phenotype was suppressed. This suppression effect was reversed upon additional depletion of MIG-15 or its binding partner NCK-1. These results suggest that both talin and the MIG-15/NCK-1 complex promote DTC motility and that MIG-38 may act as a negative regulator of the complex. We propose a model to explain the dual role of MIG-38 in motility and turning.